HUBUNGAN PERAN ORANG TUA DENGAN KEMAMPUAN TOILET TRAINING PADA ANAK USIA TODDLER DI KELURAHAN GENUK KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Yohanes Hendrik Ome; Mona Saparwati; Trimawati Trimawati (Pro Health Jurnal Ilmiah Kesehatan, 2021)
The success of toilet training for children is determined by the mother's readiness to teach toilet training and children's readiness before learning toilet training. The phenomenon of maternal behavior in toilet training varies, some train children from an early age, some get used to wearing pampers, there are also those who let their children urinate / defecate anywhere. The purpose of this study was to determine the relationship of the role of parents with the ability of toilet training in toddler age children in Genuk Village, West Ungaran District, Semarang district.Correlation design with cross sectional approach. The population of all parents of children aged 1-3 years in Genuk Village, West Ungaran District, Semarang Regency was 671 children. Subjects were 32 mother children. Sampling technique is accidental sampling. The research instrument used a questionnaire and chi square test.Most of the roles of good parents were 25 respondents (78.1%) and less than 7 respondents (21.9%). Most of the ability of toilet training in toddler age children were not able as many as 18 respondents (56.3%) and capable of as many as 14 respondents (43.8%). There was a relationship with the role of parents with the ability to toilet training for toddler aged children in Genuk Subdistrict Ungaran Barat Semarang district with a p value of 0.010 <= 0.05.Parents are expected to play an active role in educating their children to do toilet training so that they can do toilet training early.